2021
DOI: 10.1111/jcpt.13445
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Calcitonin Gene‐Related Peptide (CGRP) Antagonists: A comprehensive review of safety, efficacy and prescribing information

Abstract: What is known and objectives Migraine is a disabling disorder that affects individuals of all ages. To date, there are multiple limitations to using guidelines‐recommended treatments and preventive therapies. The goal of this review was to provide a comprehensive clinical review of the safety, efficacy and prescribing information of the emerging calcitonin gene‐related peptide (CGRP) antagonists. Agents in this new pharmacologic class were approved by the US Food and Drug Administration (FDA) for the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, ubrogepant, rimegepant and atogepant have meanwhile been approved as migraine therapeutics by the US Food and Drug Administration (FDA), and other regulatory authorities including the European Medicines Agency (EMA) were following suit in licensing these gepants. The phase 3 trials of these small molecule CGRP receptor antagonists revealed only rare and transient elevations of serum aminotransferase levels ( Croop et al, 2019 ; Dodick et al, 2019 ; Lipton et al, 2019a , b ; Ailani et al, 2020 ; Omaer et al, 2021 ) that did not lead to clinically manifest liver injury.…”
Section: Gastrointestinal Side Effect Profile Of Anti-calcitonin Gene-related Peptide Migraine Therapeutics In Pre-approval Clinical Triamentioning
confidence: 99%
See 3 more Smart Citations
“…However, ubrogepant, rimegepant and atogepant have meanwhile been approved as migraine therapeutics by the US Food and Drug Administration (FDA), and other regulatory authorities including the European Medicines Agency (EMA) were following suit in licensing these gepants. The phase 3 trials of these small molecule CGRP receptor antagonists revealed only rare and transient elevations of serum aminotransferase levels ( Croop et al, 2019 ; Dodick et al, 2019 ; Lipton et al, 2019a , b ; Ailani et al, 2020 ; Omaer et al, 2021 ) that did not lead to clinically manifest liver injury.…”
Section: Gastrointestinal Side Effect Profile Of Anti-calcitonin Gene-related Peptide Migraine Therapeutics In Pre-approval Clinical Triamentioning
confidence: 99%
“…The gepants in clinical use are in general well tolerated as proved in the RCTs during clinical development. Apart from infections of the upper respiratory, urinary and/or gastrointestinal tract, nausea (1.8–4.7% of patients on gepants) was the most common gastrointestinal complaint reported in phase 3 trials of ubrogepant, rimegepant and atogepant ( Croop et al, 2019 ; Lipton et al, 2019a , b ; Ailani et al, 2020 , 2021 ; Omaer et al, 2021 ). Diarrhea was noted in 2.5–2.7% of patients on ubrogepant ( Ailani et al, 2020 ) while constipation was reported in 6.9–7.7% of subjects taking atogepant ( Ailani et al, 2021 ), but were not noticed in the trials of the other gepants.…”
Section: Gastrointestinal Side Effect Profile Of Anti-calcitonin Gene-related Peptide Migraine Therapeutics In Pre-approval Clinical Triamentioning
confidence: 99%
See 2 more Smart Citations